The Oxford Centre for Mission Studies: A Tradition of Inquiry in Holistic Transformative Mission Scholarship - Harvey, Thomas (Transformation, 2024)
This article will consider the Oxford Centre for Mission Studies as ‘a tradition of inquiry and a coherent ‘movement of thought’. The article follows OCMS's development of mission studies over the past 40 years. It is based upon personal experience as well as on interviews with founders, academic officers, faculty, alumni, and current students: primarily in the OCMS PhD programme, but not exclusively. In sum, it is a living tale of OCMS of the ongoing embodiment of mission study as Wholistic Transformation.